Estrategias Metodológicas para la enseñanza de Estudios Sociales en Educación General Básica - Remachi Moreno, Klever Geovanny (2022)
The present investigation carried out contributes in the solution to the investigative problem that focuses on How to improve the teaching process of Social Studies in Basic General Education in the Millennium Educative Unit Santiago de Píllaro? Therefore, the objective is to develop methodological strategies for teaching Social Studies and the improvement of teaching performance. So, the mixed approach was used which allowed the systematic integration of qualitative and quantitative methods in order to obtain, collect and analyze the information of the study phenomenon, the deductive approach was applied for the theoretical analysis context then derive its effects. In the face of the problem, in the same way, theoretical methods were used, such as the analytical-synthetic one, where the research was carried out through the analysis and synthesis of the epistemological information of the methodological strategies. The type of research was: applied and practical that through the proposal strengthens teaching performance. The proposal of methodological strategies for the teaching of Social Studies was validated by experts and users, who state that it contributes effectively to the teaching work. Through the methodological strategies training workshop, the results were favorable, contributing to the strengthening of teaching performance and the academic part of the educational institution